2015
DOI: 10.2147/copd.s90534
|View full text |Cite
|
Sign up to set email alerts
|

Long-term evaluation of home-based pulmonary rehabilitation in patients with COPD

Abstract: IntroductionPersonalized, global pulmonary rehabilitation (PR) management of patients with COPD is effective, regardless of the place in which this rehabilitation is provided. The objective of this retrospective observational study was to study the long-term outcome of exercise capacity and quality of life during management of patients with COPD treated by home-based PR.MethodsHome-based PR was administered to 211 patients with COPD (mean age, 62.3±11.1 years; mean forced expiratory volume in 1 second, 41.5%±1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 53 publications
(70 reference statements)
0
40
2
Order By: Relevance
“…Our data support the conclusions of the latter authors that this is due to participants not exercising at sufficient intensity and, as our results indicate, not walking at a sufficient frequency. In contrast, in a recent cohort study of home-based PR with once weekly supervision, participants exercised for at least 5 days per week, for 30 to 45 minutes, and at a higher intensity than our participants did, resulting in a statistically and clinically significant increase in physical capacity 38. Thus, a more demanding program, if enforceable, could have produced better outcomes.…”
Section: Mwd and Physical Activitycontrasting
confidence: 75%
See 1 more Smart Citation
“…Our data support the conclusions of the latter authors that this is due to participants not exercising at sufficient intensity and, as our results indicate, not walking at a sufficient frequency. In contrast, in a recent cohort study of home-based PR with once weekly supervision, participants exercised for at least 5 days per week, for 30 to 45 minutes, and at a higher intensity than our participants did, resulting in a statistically and clinically significant increase in physical capacity 38. Thus, a more demanding program, if enforceable, could have produced better outcomes.…”
Section: Mwd and Physical Activitycontrasting
confidence: 75%
“…Second, the tele-rehab intervention may have been better delivered by health professionals, such as physiotherapists who are skilled in the management of exercise, movement, and function for people with COPD. Additionally, individuals may require prior experience of structured exercise as well as integrating this into daily activities 38. Future research may indicate how many supervised sessions are initially required.…”
Section: Mwd and Physical Activitymentioning
confidence: 99%
“… 8 11 Furthermore, a significant increase in the number of steps on the 6MST (from 488 to 570) was observed not only after outpatient PR (in agreement with previously published results in 30 COPD patients), 16 but also after home PR in a population of patients with idiopathic pulmonary fibrosis, 43 unselected patients with more severe chronic lung disease (80% on long term oxygen therapy and/or noninvasive ventilation), 17 and in COPD patients. 18 The mean improvement of 79 steps on the 6MST in this study is superior to the 40-step MCID proposed by Pichon et al 44 based on the analysis of the results of 62 COPD patients managed by inpatient PR. The performances on the two clinical exercise tolerance tests were significantly improved after PR: 79 steps on the 6MST and 42 m on the 6MWT, and these improvements were significantly correlated with each other.…”
Section: Discussioncontrasting
confidence: 60%
“… 15 , 16 The 6MST has been used to assess exercise tolerance in the context of PR. 17 , 18 However, the correlation between the 6MST and validated indices used to measure exercise capacity (6MWT and CPET) has not yet been established.…”
Section: Introductionmentioning
confidence: 99%
“…All studies found that pulmonary rehabilitation programs or individual physical therapy programs were effective in improving the quality of life [12][13][14][15][16][17], physical endurance [12][13][14][15][16][18][19][20][21][22][23], respiratory muscle strength [13,18,23], reducing symptoms of CoPd [14,16,19,23], improving the function of external breathing [16,[24][25][26], blood parameters [22,27], cognitive functions [21], functional state of muscles [28], survival rates [29,30], and reducing the number of hospital days [31]. The main part of investigations was devoted to the comparison of therapeutic rehabilitation programs that included several components and referred to stable patients with CoPd.…”
Section: Resultsmentioning
confidence: 99%